The study of the permeability of the blood-brain barrier for new neurotropic peptide drugs - V. P. Zherdev; S. S. Boyko; R. V. Shevchenko (LLC "Publisher OKI", 2019)
The paper presents the results of studies of penetration through the hemato-encephalic barrier (BBB) of rats of three new peptide drugs -modified analogues of endogenous neuropeptides and their active metabolites created in the research Zakusov institute of Pharmacology. Discussed the main physical-chemical characteristics of study dipeptides which allow predicting the penetration of peptide compounds through the BBB. All three of the studied compounds: noopept is a peptide analog of piracetam (ethyl ether N-phenylacetyl-L-prolyl-L-glycine) with nootropic and neuroprotective activity, dilept - analoge of neurotensin (methyl ether of N-caproyl-L-prolyl-L-tyrosine) - antipsychotic wich positive mnemotropic effect and the compound GB-115 (amide N-hexanoyl-L-glycyl-L-tryptophan) - retroanaloge of cholecystokinin-4 is a selective anxiolytic with anti-alcohol effect. In experiments on rats using the method of HPLC-MS/MS was shown that noopept and its metabolite cyclo-prolyl-L-glycine (CPG) are found in brain of rats after oral administration of the substance drugs, which indicates their penetration through the BBB with coefficients Kbrain/plasma 1.61 and 1.38, respectively; Dilept and its active metabolite M1, are detected in the brain of rats, which indicates the penetration of both compounds through the BBB with the coefficients the brain/plasma for dilept 2.0 and metabolite-0.5, that indicated on different mechanism of transport these compounds trough the BBB. It is shown that the anxiolytic GB-115 also penetrates through the BBB with a high coefficient Kbrain/plasma - 1.41. Thus, all three dipeptide analogues of natural neuropeptides penetrate the BBB, have a high tropicity to the brain tissue of rats, which may indicate their direct influence on the brain structures involved in the realization of pharmacological effects of these drugs.